VO2max Trainability and High Intensity Interval Training in Humans: A Meta-Analysis - Bacon, Andrew P.; Carter, Rickey E.; Ogle, Eric A.; Joyner, Michael J. (PloS one, 2013)
Endurance exercise training studies frequently show modest changes in VO2max with training and very limited responses in some subjects. By contrast, studies using interval training (IT) or combined IT and continuous training (CT) have reported mean increases in VO2max of up to ~1.0 L · min(-1). This raises questions about the role of exercise intensity and the trainability of VO2max. To address this topic we analyzed IT and IT/CT studies published in English from 1965-2012. Inclusion criteria were: 1)≥ 3 healthy sedentary/recreationally active humans <45 yrs old, 2) training duration 6-13 weeks, 3) ≥ 3 days/week, 4) ≥ 10 minutes of high intensity work, 5) ≥ 1:1 work/rest ratio, and 6) results reported as mean ± SD or SE, ranges of change, or individual data. Due to heterogeneity (I(2) value of 70), statistical synthesis of the data used a random effects model. The summary statistic of interest was the change in VO2max. A total of 334 subjects (120 women) from 37 studies were identified. Participants were grouped into 40 distinct training groups, so the unit of analysis was 40 rather than 37. An increase in VO2max of 0.51 L · min(-1) (95% CI: 0.43 to 0.60 L · min(-1)) was observed. A subset of 9 studies, with 72 subjects, that featured longer intervals showed even larger (~0.8-0.9 L · min(-1)) changes in VO2max with evidence of a marked response in all subjects. These results suggest that ideas about trainability and VO2max should be further evaluated with standardized IT or IT/CT training programs.